Pharmacokinetics, metabolite profiling, safety and tolerability of YZJ-4729 tartrate, a novel G protein-biased μ-opioid receptor agonist, in healthy Chinese subjects - Ni, Yufeng; Gao, Huaye; Ouyang, Wen; Yang, Guoping; Cheng, Minlu; Ding, Li (Frontiers in Pharmacology, 2024)
Objective: YZJ-4729 is a novel G protein-biased μ-opioid receptor agonist for the treatment of acute pain in adult patients who require intravenous opioid analgesic therapy. The aim of this study was to assess the pharmacokinetics, metabolite profiling, safety and tolerability of YZJ-4729 in healthy Chinese subjects following the single intravenous doses ranged from 0.2 mg to 6 mg.Methods: This single-center, randomized, double-blind, placebo-controlled clinical study was conducted in 54 healthy male and female Chinese subjects after single ascending doses of YZJ-4729 tartrate (0.2, 0.5, 1.5, 3, 4.5, and 6 mg). Subjects in each cohort were assigned randomly to receive a single intravenous dose of YZJ-4729 tartrate injection or placebo at a ratio of 4:1. Pharmacokinetic characteristics, metabolite profiling, safety and tolerability profiles of the study drug were evaluated.Results: Overall, YZJ-4729 was safe and well tolerated in healthy Chinese subjects. The study drug reached peak plasma concentrations nearly at the end of the infusion. After administration, YZJ-4729 was eliminated rapidly with a terminal elimination half-life of 0.862 to 2.50 h, and excreted little in human excreta. The maximum drug concentration and area under the plasma concentrationtime curve increased with dose escalation across the entire dose range, and the dose-linear pharmacokinetic profile was observed. YZJ-4729 experienced extensive metabolism in human body. A total of 19 metabolites were identified and the characteristic metabolic pathways involved hydroxylation, ketone formation, N-dealkylation and glucuronide conjugation. Metabolite M10 was the most abundant circulating metabolite, and represented over 10% of total drug-related systemic exposure. Further PK and safety evaluation of M10 was necessary.The clinical study results laid a foundation for the further clinical studies of YZJ-4729 in patients. receptors: Current status and future directions. Science Signaling 14, eaav0320. doi: 10.1126/scisignal.aav0320. China National Medical Products Administration (2012). Guidance for estimating the maximum recommended starting dose (MRSD) of drugs in the first clinical trial of healthy adult volunteers.